Ergonomic Design of Shovel to Improve Productivity in Sorghum Silage Industry - Caesaron, Dino; Ardani, Farell; Yudistira, Yudistira; Mufidah, Ilma (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
AbstractSorghum silage production is an important process in the animal feed industry. However, manually transferring chopped sorghum with existing shovels can increase workers' risk of musculoskeletal disorders. This study aimed to design an ergonomic shovel to reduce the risk of injury and improve work efficiency. The shovel design was developed based on worker anthropometric data and the Quality Function Deployment (QFD) approach. Ergonomic evaluation was conducted using the Rapid Entire Body Assessment (REBA) method, while productivity was measured based on worker energy consumption and work capacity. The results showed that the ergonomic shovel reduced the ergonomic risk score from 11 to 4, indicating a significant improvement in work posture. The average heart rate of workers after work decreased from 195–201 beats per minute to 118–122 beats per minute. Productivity increased from 1.06–1.13 kg/kcal to 4.09–4.41 kg/kcal, indicating increased work energy efficiency. The shovel's ergonomic design has a 72 cm handle length, 3 cm handle diameter, and stainless steel material, which has proven more comfortable to use and reduces the worker's physiological burden. This study's results confirm that applying ergonomic principles in designing work tools can improve worker welfare and the efficiency of the sorghum silage industry. Further test is needed for validation on a broader scale.Keywords: ergonomics, musculoskeletal disorders, productivity, sorghum silage, tool design AbstrakProduksi silase sorgum merupakan proses penting dalam industri pakan ternak. Aktivitas pemindahan manual irisan sorgum dengan sekop eksisting dapat meningkatkan risiko gangguan muskuloskeletal pada pekerja. Penelitian ini bertujuan merancang sekop ergonomis untuk mengurangi risiko cedera dan meningkatkan efisiensi kerja. Desain sekop dikembangkan berdasarkan data antropometri pekerja serta pendekatan Quality Function Deployment (QFD). Evaluasi ergonomi dilakukan menggunakan metode Rapid Entire Body Assessment (REBA), sedangkan produktivitas diukur berdasarkan konsumsi energi dan kapasitas kerja pekerja. Hasil penelitian menunjukkan bahwa sekop ergonomis menurunkan skor risiko ergonomi dari 11 menjadi 4 yang mengindikasikan perbaikan postur kerja yang signifikan. Rata-rata denyut nadi pekerja setelah bekerja menurun dari 195–201 denyut per menit menjadi 118–122 denyut per menit. Produktivitas meningkat dari 1,06–1,13 kg/kkal menjadi 4,09–4,41 kg/kkal, menunjukkan peningkatan efisiensi energi kerja. Desain ergonomis sekop dengan panjang gagang 72 cm, diameter pegangan 3 cm, serta material baja tahan karat terbukti lebih nyaman digunakan dan mengurangi beban fisiologis pekerja. Hasil penelitian ini memastikan bahwa penerapan prinsip ergonomi dalam desain alat kerja dapat meningkatkan kesejahteraan pekerja dan efisiensi industri silase sorgum. Pengujian lebih lanjut diperlukan untuk validasi dalam skala yang lebih luas.Kata kunci: desain alat, ergonomi, gangguan muskuloskeletal, produktivitas, silase sorgum